Towards best practice for assessing the impacts of climate change on groundwater - Holman, Ian P.; Allen, D. M.; Cuthbert, M. O.; Goderniaux, P. (Springer, 2012)
An essay is presented on the recommendations that need to be considered by hydrogeologists in assessing the impacts of climate change on groundwater. It says that the use of climate model projections must consider the utilization of multiple global climate models (GCMs) and regional climate models (RCMs), multiple emission scenarios, and the implication of downscale method. The different recommendations for developed hydrogeological coupling and socio-economic considerations are also mentioned.